A Home for Life? A Critical Perspective on Housing Choice for "Downsizers" in the UK. (April 2016) - Adam, Park; Friederike, Ziegler
Abstract : A range of policy, research and media commentary has highlighted the link between housing, health, and wellbeing in later life, with discourses around "ageing in place" and "downsizing" emerging as particularly dominant. Proponents of "downsizing" strategies argue that the motivation for older people should be self-evident: difficulties with maintenance, heating bills, getting upstairs, and the increasing risk of falls are all commonly referred to. This outlook also highlights the economic benefits of downsizing to "age-appropriate" housing, particularly in relation to potential savings for health and social care budgets. Drawing upon participatory research with older people in the city of Sheffield, UK, this paper critiques current practices and discourses around the commissioning, design, and management of purpose-built retirement housing. The paper calls for an urgent need to reframe housing from a lifecourse perspective and to recognize older people as active citizens, for whom their homes are essential to their continuing to contribute to family life and society. We argue for a more nuanced debate around "downsizing" and "ageing in place", and call for policy-makers to recognize the risk of spatially and socially marginalizing older people through current limitations in housing choices. The paper concludes by setting out a number of measures to improve the choice, quality, and flexibility of housing for later life.